Penerapan Asas Ultimum Remedium terhadap Penyimpangan Pengadaan Barang/Jasa Pemerintah dalam Perspektif Kepastian Hukum di Tengah Kabut Epistemik - Andi Juana Fachruddin; Haedar Djidar; Abdul Rahman (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Corruption law enforcement within Indonesia’s government procurement sector (PBJP) is currently ensnared in an "epistemic fog," leading to the blurring of boundaries between administrative and criminal law regimes. The historical superiority of the Anti-Corruption Law frequently negates administrative law doctrines, resulting in administrative faults being reconstructed as corruption offenses through a rigid interpretation of Article 4. This study aims to reconstruct the law enforcement paradigm through the integration of attribution theory and the synchronization of norms between Article 613(c) of Law No. 1 of 2023 (The National Penal Code), as further mandated by Law No. 1 of 2026 concerning the Procedures for Criminal Application, and Article 77 of Presidential Regulation No. 46 of 2025. Utilizing a normative-juridical method, this research finds that asset recovery mechanisms through administrative channels (TP/TGR) constitute a conditio sine qua non that must precede criminal prosecution. The novelty of this study lies in the argument that the integration of Article 613c Law 1/2023 and Law 1/2026 functions as lex posterior derogat legi priori, effectively repositioning the rigid nature of Article 4 of the Anti-Corruption Law, whereby administrative recovery eliminates the material nature of criminal unlawfulness in procurement cases.